Porqué lo educativo es y será cada vez más aburrido - Proa, Sergio Espinosa (Boletim Técnico do Senac, 2003)
Under the pretext of analyzing the book Education and Professional Formation, by Antonio Alanís Huerta, the article criticizes the ‘mania’ of giving everything an answer that characterizes education. In the contemporary world, said globalized, this mania becomes a sort of hard fitting-in to what His Majesty, the Market, requires: productivity, efficacy, quality, and merit. Is it education? Or, contrariwise, only the question, ‘the deepness without hope of a question’ would be able to say something new, different from what all of us already know and already think and already hate ‘in the most educated manner’?.